2011
DOI: 10.1007/s10584-011-0181-y
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of snow cover changes in the Himalayan region using MODIS snow products and in-situ temperature data

Abstract: Amidst growing concerns over the melting of the Himalayas' snow and glaciers, we strive to answer some of the questions related to snow cover changes in the Himalayan region covering Nepal and its vicinity using Moderate Resolution Imaging Spectroradiometer (MODIS) snow cover products from 2000 to 2008 as well as in-situ temperature data from two high altitude stations and net radiation and wind speed data from one station. The analysis consists of trend analysis based on the Spearman's rank correlation on mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 25 publications
6
58
0
2
Order By: Relevance
“…These mapping exercises indicated that remote-sensing (RS) data and geographic information system (GIS) tools are more reliable for snow cover mapping. Further snow cover and glacier change research has been carried out using various methods, datasets and techniques in Nepal in a major part of the Himalayan regions (Armstrong 2010;Bolch et al 2012), as well as at the national level (Shrestha and Joshi 2009;Bajracharya et al 2014) or at a smaller scale (Maskey et al 2011;Shrestha et al 2012;Kuhle 2014;Shea et al 2014). The overall small-scale mapping of various classes of LULC in Nepal is summarized in the Table 2, with LULC categories, spatial and temporal coverage, sources of data and references.…”
Section: Study Area Sources Of Data and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These mapping exercises indicated that remote-sensing (RS) data and geographic information system (GIS) tools are more reliable for snow cover mapping. Further snow cover and glacier change research has been carried out using various methods, datasets and techniques in Nepal in a major part of the Himalayan regions (Armstrong 2010;Bolch et al 2012), as well as at the national level (Shrestha and Joshi 2009;Bajracharya et al 2014) or at a smaller scale (Maskey et al 2011;Shrestha et al 2012;Kuhle 2014;Shea et al 2014). The overall small-scale mapping of various classes of LULC in Nepal is summarized in the Table 2, with LULC categories, spatial and temporal coverage, sources of data and references.…”
Section: Study Area Sources Of Data and Methodsmentioning
confidence: 99%
“…This has been verified by the Himalayan region annual glacier retreat rate, reported as 0.3−1m, the highest rate in the world (Dyurgerov and Meier 2005). Many studies (regional, national and small-scale) have been carried out on Nepal's snow/glacier cover changes Kadota et al 1997;Nie et al 2010;Lamsal et al 2011;Maskey et al 2011;Bolch et al 2012;Bajracharya et al 2014), which all examine the changing situation of snow/glacier cover in the country.…”
Section: Forest Land Changementioning
confidence: 99%
See 1 more Smart Citation
“…June-August and autumn, i.e. September-November) following schema adopted by Immerzeel et al, 2009 andMaskey et al, 2011. Intra-annual variability is important for water users like hydropower sector and farming community to understand the changes and adapt, average monthly SCAs spanning a 10-year period were plotted, and variations within individual months were captured by standard deviations (SDs) using 10 sets of monthly average SCAs.…”
Section: Snow Cover Area Analysismentioning
confidence: 99%
“…The study also aims at estimating snowmelt runoff contribution to the annual discharge at the Thalot site. MOD10A2 comes in a spatial resolution of 500*500 m 2 in every 8-day period that begins on the first day of each year and extends to the first few days of the next year, (Maskey et al, 2011).…”
Section: Introductionmentioning
confidence: 99%